2016
DOI: 10.3171/2015.10.spine141261
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral compression fractures after stereotactic body radiation therapy: a large, multi-institutional, multinational evaluation

Abstract: OBJECTIVE The purpose of this study was to identify factors contributing to an increased risk for vertebral compression fracture (VCF) following stereotactic body radiation therapy (SBRT) for spinal tumors. METHODS A total of 594 tumors were treated with spinal SBRT as primary treatment or re-irradiation at 8 different institutions as part of a multi-institutional research consortium. Patients underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 29 publications
4
52
0
Order By: Relevance
“…Similar rates of preexisting VCFs (24%) were detected in a large retrospective study of 594 treated spinal tumors by Jaward et al [21]. VCF rates in relevant studies varies between 7 and 39% [2226].…”
Section: Discussionsupporting
confidence: 70%
“…Similar rates of preexisting VCFs (24%) were detected in a large retrospective study of 594 treated spinal tumors by Jaward et al [21]. VCF rates in relevant studies varies between 7 and 39% [2226].…”
Section: Discussionsupporting
confidence: 70%
“…3,5,8,15,17,20 Median follow-up in these publications ranges from 7 to 15 months, with a median or mean time to fracture between 2 and 25 months. All studies reported an increased risk of fracture in patients with lytic metastases.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,17 Individual studies have also cited increasing dose per fraction, age > 55 years, increasing vertebral body tumor involvement, thoracolumbar junction and lumbar level metastases, tumor progression, lung and/or hepatocellular histology, solitary metastases, and lack of MRI for treatment planning as risk factors for VCF. 3,5,8,15,17,20 Variability in patient selection, fracture detection, presence of tumor, follow-up, and radiation methods may account for the wide range in the reported radiographic fracture risk and time to fracture. A paucity of data relates to the symptomatology of post-SRS VCF, with most of the above-mentioned studies reporting radiographic VCF progression rather than VCF-associated symptomatology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 15 studies identified are listed in Table 2 with the relevant findings. 10,19,20,[22][23][24][25][26][27][28][29][30][31][32][33] The majority involved patients with diverse primary tumour locations or histologies. Thibault et al focused specifically on patients with renal cell carcinoma (RCC) metastases, and Yoo et al only reported lesions from hepatocellular carcinoma (HCC) origin.…”
Section: Resultsmentioning
confidence: 99%